Fulfillment of Consumer Rights to Information Regarding Flight Delays: A Case Study of Batik Air Passengers - Evi Marpaung (Universitas Negeri Semarang, 2026)
This study aims to analyze the position of consumers' rights to departure information in the provision of air transportation services and to examine the legal responsibility of airlines for uncertainty of information that results in flight delays. The main problem lies in the discrepancy between normative regulations regarding the obligation to provide information and service practices in the field, particularly in the case of Batik Air passengers who experienced repeated schedule changes without adequate explanation. This study uses a normative juridical method with a legislative and conceptual approach, through analysis of relevant legislation, principles, and legal doctrines. The results of the study show that the right to departure information has a fundamental position in consumer protection law, administrative law in aviation law, and contractual law in air transportation agreements. Uncertainty in information that is conveyed in an unclear and inconsistent manner can be qualified as improper performance (breach of contract) and gives rise to legal liability for the airline. In conclusion, airlines are not only obliged to provide minimum administrative compensation, but are also required to ensure transparency, certainty, and accountability of information as an integral part of the quality of air transportation services.